Using word mapping strategy for improving english vocabulary with 8th year students in parallel C at Adolfo Valarezo public high school, academic period 2013-2014 - Gonzalez Betancourt, Mashury Cristina (2015)
This descriptive study investigated the improvement of the vocabulary with the use of word mapping strategy with 8th-C year students at Adolfo Valarezo public high school. An intervention plan with five sessions was carried out to improve the vocabulary. Two researcher-made tests and questionnaires were designed to assess the thirty seven students’ progress and perception of word mapping use. Additional instruments such as Checklists were also used every session to record the students’ achievement. The findings indicated that the use of word mapping strategy facilitated meaningfully the improvement of vocabulary, which was reflected in the noticeable increase of the posttest scores and students’ progress during the intervention. It would be fair to conclude that this action research helped the students to improve their vocabulary and helped the researcher to sharpen her teachings skills.